TECHNOLOGY OF DIFFERENTIATED APPROACH IN THE FORMATION OF COGNITIVE-SPEECH KNOWLEDGE AND SKILLS IN STUDENTS WITH HEARING IMPAIRMENTS - Urunova Zakhro Nizamitdinovna; Abdukadirova Mukhlisa (Zeta Repository, 2023)
At present, in special education, along with traditional teaching methods, the use of interactive approach technologies in the formation of cognitive-speech knowledge and skills in students with hearing impairments is spreading. In this article, we propose as a technology for an interactive approach in the formation of cognitive-speech knowledge and skills in students with hearing impairments to organize lessons using visual communication tools, that is, video content, through which you can expand learning opportunities.